2019
DOI: 10.1111/ipd.12482
|View full text |Cite
|
Sign up to set email alerts
|

Impact of molar incisor hypomineralization on quality of life in children with early mixed dentition: A hierarchical approach

Abstract: Background Molar incisor hypomineralization (MIH) is associated with unfavourable dental conditions such as dental caries and may consequently impact oral health‐related quality of life (OHRQoL). Objective To assess the impact of MIH on OHRQoL in children with early mixed dentition. Method A population‐based cross‐sectional study of 728 8‐year‐old children from the public school system in Curitiba, Brazil, was conducted. The Child Perception Questionnaire for 8‐ to 10‐year‐olds (CPQ8‐10) was used to evaluate O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
1
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 22 publications
11
66
1
10
Order By: Relevance
“…In a recent study, it has been reported that MIH has an impact on all areas among Colombian children aged 7‐10 years . Portella et al similarly reported that the effect of MIH on OHRQoL was in the oral symptoms of the child.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent study, it has been reported that MIH has an impact on all areas among Colombian children aged 7‐10 years . Portella et al similarly reported that the effect of MIH on OHRQoL was in the oral symptoms of the child.…”
Section: Discussionmentioning
confidence: 97%
“…MIH can impair OHRQoL by causing functional limitations . It was reported that children with severe MIH showed a more negative impact on OHRQoL regarding oral symptoms and functional limitation areas than those without MIH .…”
Section: Discussionmentioning
confidence: 99%
“…The sample consisted of 356 school children, which were randomly selected from a representative population [58] from the city of Curitiba public schools. To ensure accurate population representation, two-stage cluster sampling was performed.…”
Section: Cohort From Curitiba Brazil (Federal University Of Paraná):mentioning
confidence: 99%
“…e association between the presence of MIH and quality of life has been previously reported in some studies both in Brazil [12,13] and in other countries, such as Colombia [1] and Mexico [14]. However, given the existence of particularities in the occurrence and comorbidities associated with MIH [5,8,15,16], this relationship needs to be investigated in more detail, considering its cultural and socioeconomic diversities [17].…”
Section: Introductionmentioning
confidence: 94%